A Brief Bibliometric Survey on Circularly Polarized Antennas for Mobile Communication - Gunjal, Aniket; Singh, Abhaya Pal (Library philosophy and practice, 2020)
This paper presents a database review on "Circularly Polarized Antennas for Mobile Communication" as it is the emerging technique used by mobile service provider because of having benefits over other types of antennas available.The polarization purity is now the major issue. In some cases due to cross polarization issue the antenna signal is cancelled at receiver side.So, it is necessary to have circularly polarized antenna to avoid this polarization issue because of change in phase of signal. The change in phase of signal is due to striking of wave on the obstacles and it slightly tilted from its direction causes cross coupled radiation at receiver's side. The phase change causes loss of signal as the wave is directly cancelled by the receiver antenna. The necessity of doing this bibliometric survey is that to know how the circular polarization is advantageous for today's mobile communication systems and its practical usability.This paper shows the importance of circular polarization antenna from the year 1992 and continued upto the present date. The database analysis of the antennas is done through Scopus, Google Scholar and tools like Gephi and GPS Visualizer etc.Through this database survey it is revealed that maximum number of publications are from conferences and journals, affiliated to engineering, Chinese lead publications followed by Japan and then India. Axial ratio bandwidth is the second important parameter. For gain and radiation pattern keywords, after the engineering computer science is the most contributing subject area and least contribution in terms of review papers is also found.